DDRE-23. PRECLINICAL EVALUATION OF BRAIN PENETRATION PROPERTIES OF NEW FIRST-IN-CLASS LYSINE-SPECIFIC DEMETHYLASE 1 (LSD1) INHIBITOR, SP-2577. (12th November 2021) - Jiang, Jun; Hopkins, Barbara; Hook, Garry; Melendez, Ernesto Luna; Tovmasyan, Artak; Mehta, Shwetal; Li, Jing; Sanai, Nader
Abstract: BACKGROUND: Lysine specific demethylase 1 (LSD1) is a histone demethylase implicated in the maintenance of pluripotency and proliferation gene programs that give rise to a number of cancers. SP-2577 is a first-in-class selective and reversible inhibitor of LSD1. Here, we evaluated the ability of SP-2577 to cross blood-brain barrier in mouse brain. METHODS: Fifteen BALB/c mice were treated with 50 mg/kg SP-2577 twice daily intraperitoneally for 4 days. At 2, 6, and 12 hours after the last treatment dose was delivered, plasma and brain samples were collected for analysis of SP-2577 bound and unbound fractions (5 mice/time point). An LC–MS/MS method was developed to measure the drug levels in mouse plasma and brain. The unbound fractions of SP-2577 in plasma and brain tissue were determined using equilibrium dialysis. RESULTS: Total plasma levels of SP-2577 at the 2, 6, and 12-hour time points following the last dose were 1353 nM, 1209 nM, and 560 nM, accordingly. Total drug levels in brain measured at the same time points were 276 nM, 183 nM, and 168 nM. SP-2577 is highly bound to plasma proteins and brain tissue components with an average plasma unbound fraction value of 0.009. Unbound levels of SP-2577 were undetectable in brain tissue, potentially due to instability of the drug in brain homogenates. The total brain-to-plasma ratio (Kp) was determined as 0.032 (range, 0.027–0.046) in mice. CONCLUSION: SP-2577 is well tolerated in mice and achieves reasonable total drug levels in mouse brain, yet is highly-bound to plasma proteins and brain components. Taken together, these data indicate that SP-2577 cannot reach pharmacologically-relevant drug concentrations across the mouse blood-brain barrier.